Personal excellence - Munroe, Myles (U.S.A: Destiny Image Publisher, 2013)
Personal excellence is a complete, integrated, principles-centred approach to releasing the awesome potential trapped within you. With penetrating insights and pointed anecdotes, this DVD reveals a step-by-step pathway to releasing your potential. If you have been frustrated by your dreams, ideas, and visions, this DVD will activate your buried treasure and ignite the wheels of productivity. It will release a death blow to procrastination and set you on a path to personal fulfillment, purpose, and productivity. Personal excellence will enable you to: Activate, stimulate, and release the wealth of your potential. Break free and leap over the limitations of past opinions, failures, and disappointments. Comprehend and appropriate the principle keys for unleashing the wealth of potential trapped inside you destined for the next generation.